Seasonal Indoor Radon Assessment and Estimation of Cancer Risk: A Case Study of Obafemi Awolowo University Nigeria - Deborah Tolulope Esan; Yinka Ajiboye; Rachel Obed; Babakayode Babajide Olubodun; James Enajero Tobih (SAGE Publishing, 2024)
Human exposure to indoor radon has been a subject of continuous concern due to its health implications, especially as it relates to lung cancer. Radon contaminates indoor air quality and poses a significant health threat if not abated/controlled. A seasonal indoor radon assessment of residential buildings of Obafemi Awolowo University was carried out to determine radon seasonal variability and to evaluate the cancer risk to the residents. AT-100 diffusion-based track detectors were deployed within living rooms and bedrooms for the radon measurement. During the rainy season, the average indoor radon concentration was 18.4 ± 10.1 Bq/m 3 , with higher concentrations observed in bedrooms compared to living rooms, whereas the average radon concentration was 19.0 ± 4.4 Bq/m 3 in the dry season, with similar radon levels in living rooms and bedrooms. The potential alpha energy concentration values ranged from 1.62 to 7.57 mWL. The annual effective dose equivalent values were below the world average and recommended limits for public exposure. Of the three geological units underlying the residences, the buildings overlying the granite gneiss lithology have the highest radon concentrations with average value of 21.4 Bq/m 3 . The soil gas radon concentration to indoor radon concentration ratio over the granite gneiss lithology is 0.006. The estimated average lifetime cancer risk due to radon inhalation in the residences indicated a potential risk of cancer development in 178 persons in 100 000 population over a lifetime period. The average indoor radon concentrations were below the recommended limit, requiring no immediate remediation measures. Improved ventilation of residential apartments is recommended to minimize residents' risk to indoor radon.